Guide for Road Safety Opportunities and Challenges : Low and Middle Income Country Profiles - World Bank (World Bank, Washington, DC, 2020)
Low, and middle-income countries (LMICs) are facing a major challenge in road safety. Each year, 1.35 million people are killed on the worlds’ roads, and a further 50 million are injured, with the vast majority of these (over 90 percent) occurring in LMICs. There is an upward trend in road crash fatalities and injuries, causing human suffering, grief, and loss, and retarding the economic growth of LMICs. One major barrier to improving this situation is a lack of understanding of the current problem due to deficient information. Many vital metrics of road safety performance are not measured effectively in most LMICs, including critical intermediate outcomes which guide road safety interventions and the most fundamental outcome measures: actual number of road crash fatalities and injuries. This situation generates limitations in every aspect of road safety management and delivery, including resource allocation, advocacy, intervention selection, and prioritization of resources. The globally accepted best-practice approach to addressing the road safety crisis is the Safe System approach. This consists of a system of ‘pillars’ working together to eliminate death and serious injury. Information is required on progress against each of these pillars in order to understand current deficiencies and opportunities in road safety activity, to plan a response to the crisis, to help set ambitious targets for improvement, and to monitor progress towards these targets and thus develop advocacy for and commitment to the interventions which work. This report provides country profiles with information across each Safe System pillar from LMICs in order to directly address these issues. The data to provide these reports were collected from multiple sources, as documented in this report, and are provided foreach LMIC and region where available.